Overexpression of a gibberellin 20-oxidase gene in poplar xylem led to an increase in the size of nanocellulose fibrils and improved paper properties - Xiaopeng Peng; Botong Tong; Jongcheol Lee; Kun Wang; Xiaojuan Yu; Xiong Huang; Jialong Wen; Mohamadamin Makarem; Hongying Pang; Subin Hinjan; Xiaojing Yan; Shuangquan Yao; et al. (Carbohydrate Polymers, 2023)

Understanding the Physicochemical Characteristics and the Improved Enzymatic Saccharification of Corn Stover Pretreated with Aqueous and Gaseous Ammonia - Chang Geun Yoo; Hoon Kim; Fachuang Lu; Ali Azarpira; Xuejun Pan; Kyeong Keun Oh; Jun Seok Kim; John Ralph; Tae Hyun Kim (BioEnergy Research, 2016)
Physicochemical characteristics of corn stover pretreated by soaking in aqueous ammonia (SAA) and low-moisture anhydrous ammonia (LMAA) were compared and investigated. The glucan digestibility of the treated biomass reached 90 % (SAA) and 84 % (LMAA). The LMAA pretreatment enhanced the digestibility by cleaving cross-linkages between cell wall components, whereas the SAA pretreatment additionally improved the digestibility by efficiently removing a major portion of the lignin under mild reaction conditions without significant loss of carbohydrates. Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), and gel permeation chromatography (GPC) revealed the structural and chemical transformations of lignin during the pretreatments. Both pretreatments effectively cleaved ferulate cell wall cross-linking that is associated with the recalcitrance of grass lignocellulosics toward enzymatic saccharification. Extracted lignin from SAA pretreatment was extensively depolymerized but retained “native” character, as evidenced by the retention of β-ether linkages.

Naturally p-Hydroxybenzoylated Lignins in Palms - Fachuang Lu; Steven D. Karlen; Matt Regner; Hoon Kim; Sally A. Ralph; Run-Cang Sun; Ken-ichi Kuroda; Mary Ann Augustin; Raymond Mawson; Henry Sabarez; Tanoj Singh; Gerardo Jimenez-Monteon; et al. (BioEnergy Research, 2015)

Catalytic Alkaline Oxidation of Lignin and its Model Compounds: a Pathway to Aromatic Biochemicals - Ali Azarpira; John Ralph; Fachuang Lu (BioEnergy Research, 2014)

Grass lignin acylation: p-coumaroyl transferase activity and cell wall characteristics of C3 and C4 grasses - Ronald D. Hatfield; Jane M. Marita; Kenneth Frost; John Grabber; John Ralph; Fachuang Lu; Hoon Kim (Planta, 2009)

Ferulate–coniferyl alcohol cross-coupled products formed by radical coupling reactions - Aiping Zhang; Fachuang Lu; Runcang Sun; John Ralph (Planta, 2009)

Evidence for cleavage of lignin by a brown rot basidiomycete - Daniel J. Yelle; John Ralph; Fachuang Lu; Kenneth E. Hammel (Environmental Microbiology, 2008)
Summary Biodegradation by brown‐rot fungi is quantitatively one of the most important fates of lignocellulose in nature. It has long been thought that these basidiomycetes do not degrade lignin significantly, and that their activities on this abundant aromatic biopolymer are limited to minor oxidative modifications. Here we have applied a new technique for the complete solubilization of lignocellulose to show, by one‐bond 1 H‐ 13 C correlation nuclear magnetic resonance spectroscopy, that brown rot of spruce wood by Gloeophyllum trabeum resulted in a marked, non‐selective depletion of all intermonomer side‐chain linkages in the lignin. The resulting polymer retained most of its original aromatic residues and was probably interconnected by new linkages that lack hydrogens and are consequently invisible in one‐bond 1 H‐ 13 C correlation spectra. Additional work is needed to characterize these linkages, but it is already clear that the aromatic polymer remaining after extensive brown rot is no longer recognizable as lignin.

Formation of syringyl-rich lignins in maize as influenced by feruloylated xylans and p-coumaroylated monolignols - John H. Grabber; Fachuang Lu (Planta, 2007)

Peroxidase-dependent cross-linking reactions of p-hydroxycinnamates in plant cell walls - John Ralph; Mirko Bunzel; Jane M. Marita; Ronald D. Hatfield; Fachuang Lu; Hoon Kim; Paul F. Schatz; John H. Grabber; Hans Steinhart (Phytochemistry Reviews, 2004)

Lignins: Natural polymers from oxidative coupling of 4-hydroxyphenyl- propanoids - John Ralph; Knut Lundquist; Gösta Brunow; Fachuang Lu; Hoon Kim; Paul F. Schatz; Jane M. Marita; Ronald D. Hatfield; Sally A. Ralph; Jørgen Holst Christensen; Wout Boerjan (Phytochemistry Reviews, 2004)

A new Arabidopsis thaliana mutant deficient in the expression of O-methyltransferase impacts lignins and sinapoyl esters - Thomas Goujon; Richard Sibout; Brigitte Pollet; Bruno Maba; Laurent Nussaume; Nicole Bechtold; Fachuang Lu; John Ralph; Isabelle Mila; Yves Barrière; Catherine Lapierre; Lise Jouanin (Plant Molecular Biology, 2003)